MENG, LINGZI. Gender in Literary Translation: A Corpus-Based Study of the English Translations of Chenzhong De Chibang. Singapore: Springer, 2019, 169 p. - Melo, Jinnye Altamira de Paiva; Freitas, Luana Ferreira de (Revista de Letras, 2020)
RESENHA